Nursing Leadership Perceptions of Clinical Pathways After Transitioning to an Electronic Health Record in the Acute Care Setting - Harper, Alison (Université d'Ottawa / University of Ottawa, 2022)
Background: Both clinical pathways (CPs) and electronic health records (EHRs) increase the quality and efficiency of health care; however, no known studies have examined the integration of CPs into the EHR during an organizational EHR launch. Aim: To understand how nursing leadership perceives the nursing practice changes that accompanied the transition from paper to EHR-based CPs. Methods: A case study design was utilized, focusing on CPs utilized by one acute care unit within a tertiary care organization. Findings: Transfer of paper CPs into an EHR not built for the Canadian health care context proved to be difficult. In the integration process, a single paper document became spread throughout the EHR. EHR-based CPs are not as clear, and represent a larger documentation burden, than their paper counterparts. Conclusion: Nursing agency has been greatly affected by the change in format of CPs. Further exploration of nursing agency regarding CPs is warranted.
Keywords: Clinical Pathways; Electronic Health Record; Acute Care; Nursing